Integrasi Artificial Intelligence (AI) sebagai Co-Counselor dalam Praktik E-Counseling - Sofia Rasyidah Salsabila; Rumaysha Latifah (MUTIARA: Jurnal Ilmiah Multidisiplin Indonesia, 2026)
The advancement of digital technology has accelerated the adoption of Artificial Intelligence (AI) in e-counseling services to address the growing demand for mental health support in the digital era. The increasing number of clients, counselors’ limited availability, and the challenges associated with conducting psychological assessments through online platforms have created a pressing need for innovative solutions. This study aims to examine the role of AI as a co-counselor, evaluate the effectiveness of its integration into e-counseling practices, and identify the challenges associated with its implementation. The study employed a Narrative Literature Review method by critically analyzing relevant scholarly publications. The findings indicate that AI functions as a collaborative partner that assists counselors in assessment processes, data analysis, emotion detection, service documentation, and the continuous monitoring of clients’ psychological conditions. The integration of AI has been shown to enhance the efficiency, accessibility, and overall quality of digital counseling services. However, its implementation continues to face significant challenges related to data privacy, information security, algorithmic bias, and limitations in understanding cultural contexts and human empathy. The novelty of this study lies in its comprehensive conceptualization of AI as a co-counselor that supports the entire e-counseling service cycle through a collaborative model integrating the analytical capabilities of technology with the humanistic competencies of counselors, thereby fostering more effective, ethical, and inclusive counseling services.